THE PUBLIC RELATION COMMUNICATION STRATEGY OF THE MINISTRY OF AGRARIAN AND SPATIAL/THE NATIONAL LAND AGENCY IN SOCIALIZ PENDAFTARAN TANAH SISTEMATIK LENGKAP (PTSL) - Soraya Nurida; Raka Sapto Arianda (Pimpinan Cabang Muhammadiyah Kramat Jati, 2020)
The low registration and certification of land became one of the principal issues to be dealt with by the Ministry of Agrarian and Spatial/National Land Agency (ATR/BPN) in improving the medium-term national development assisted with the existence of a Pendaftaran Tanah Sistematik Lengkap (PTSL). The role of public relations in making communication strategy for this program in order to socialize and to be understood by the community is very important. This research aims to know the communication strategy of public relations in disseminating and know what obstacles occurred in running the program. The methods used in this research is descriptive qualitative with in-depth Interview as a method of gathering data and information. Based on the results of this research it can be concluded that the communication strategy used Ministry of ATR/BPN in disseminating PTSL is by using social media, websites and the surrender of the certificate directly by the President and assisted by regional offices (REGIONAL OFFICE) to assist in disseminating PTSL program. Barriers experienced by a lack of human resources and costs in disseminating these programs. However, it was not to be a hindrance in the running of program PTSL.